ANALISIS SENGKETA HASIL PILKADA DI MAHKAMAH KONSTITUSI - Putra, Livia Sikmon; Khairazi, Fauzan (CENDEKIA: Jurnal Ilmu Pengetahuan, 2025)
The resolution of disputes over the election results of Governors, Regents, and Mayors is a crucial aspect of Indonesia’s electoral system as it directly relates to the legitimacy of election outcomes, legal certainty, and the enforcement of justice for all parties involved. This study is a legal research (legal research) employing four approaches: statute approach, conceptual approach, analytical approach, and comparative approach. These approaches are used to examine legislation, legal theories and doctrines, as well as the practice of resolving Pilkada disputes at the Constitutional Court and other related electoral institutions. The findings indicate that the legal framework governing Pilkada disputes is not yet comprehensive, and there is still overlapping authority among the institutions responsible for dispute resolution. Moreover, electoral organizers are not yet fully professional, independent, or transparent. This situation causes legal uncertainty, may reduce public trust, and weakens the protection of the constitutional rights of election participants. Therefore, regulatory reform and institutional strengthening are required to establish a dispute resolution mechanism that is effective, fair, transparent, and consistent with constitutional principles. ABSTRAK Penyelesaian sengketa hasil pemilihan Gubernur, Bupati, dan Wali Kota merupakan aspek penting dalam sistem pemilihan umum di Indonesia karena berkaitan langsung dengan legitimasi hasil pemilu, kepastian hukum, dan tegaknya prinsip keadilan bagi seluruh pihak. Penelitian ini merupakan penelitian hukum (legal research) dengan menggunakan empat pendekatan, yaitu statute approach, conceptual approach, analytical approach, dan comparative approach. Pendekatan ini digunakan untuk menelaah peraturan perundang-undangan, teori dan doktrin hukum, serta praktik penyelesaian sengketa Pilkada di Mahkamah Konstitusi dan lembaga penyelenggara pemilu terkait. Hasil penelitian menunjukkan bahwa pengaturan hukum mengenai sengketa Pilkada belum komprehensif dan masih terdapat tumpang tindih kewenangan antar lembaga penyelesai sengketa. Selain itu, penyelenggara pemilu belum sepenuhnya profesional, independen, dan transparan. Kondisi ini menimbulkan ketidakpastian hukum, berpotensi mengurangi kepercayaan publik, dan melemahkan perlindungan hak konstitusional peserta pemilihan. Oleh karena itu, diperlukan reformulasi regulasi dan penguatan kelembagaan guna menciptakan mekanisme penyelesaian sengketa Pilkada yang efektif, adil, transparan, dan konsisten dengan prinsip konstitusional.